2001
DOI: 10.2225/vol4-issue3-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma aureoviride 7-121, a mutant with enhanced production of lytic enzymes: its potential use in waste cellulose degradation and/or biocontrol

Abstract: A mutant of the native fungus Trichoderma aureoviride, 7-121, selected for its overproduction of extracellular cellulase and ß-glucosidase (cellobiase) was obtained. In shake flask cultures, production of endoglucanase, filter paper activity and cellobiase increased two to four-fold as compared with the wild type strain. The mutant strain is stable and grows rapidly in liquid as well as in solid culture media. Enzyme yields were best when pH was controlled so that it did not fall bellow pH 3.5. Cellobiase prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
3
41
0
1
Order By: Relevance
“…Cellulase is an inducible enzyme complex involving synergistic action of endoglucanase (C x ), exoglucanase (C 1 ) and cellobiase (C B ) (Zaldivar et al, 2001). The high cost of cellulase production owing to use of pure chemicals in production coupled with low enzyme activities limits its industrial use (Kalra and Banta, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulase is an inducible enzyme complex involving synergistic action of endoglucanase (C x ), exoglucanase (C 1 ) and cellobiase (C B ) (Zaldivar et al, 2001). The high cost of cellulase production owing to use of pure chemicals in production coupled with low enzyme activities limits its industrial use (Kalra and Banta, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulomonas flavigena enzyme was found to have optimum cellulase and xylanase activities at pH 6 with an optimum temperature at 50 0 C (Perez- Avalos et al, 2008). Zaldivar et al (2001) observed that cellulase production by Trichoderma aureoviridae is best if pH doesn't fall below 3.5 and at an optimum temperature of 28 0 C. Pei-Jun et al (2004) reported a pH of 6.5 for optimum cellulase production by Trichoderma. koningii.…”
Section: Introductionmentioning
confidence: 99%
“…Gadgil et al (1995) reported that mutation may not only effect the cellulase genes directly but also affect the synthesis and secretion of the chitinase and cellulase (Limon et al, 1999). Also, Zaldivar et al (2001) observed an increase in production of endoglucanase, filter paper activity and cellobiase in two to fourfold of mutated T. aureoviride 7-121 as compared with the wild type strain. Induction of mutagenesis by gamma irradiation can also increase the ability of Trichoderma species to produce antibiotics and phenolic compounds such as trichodermine, gliotoxin and viridian (Haggag and Mohamed, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…There are numerous enzymes that M. roridum can produce and release onto the water hyacinth leaf such as cellulases enzymes which hydrolyze the β-1,4-Dglycosidic bonds within the cellulose molecules of plant (Akiba et al, 1995;Baer and Gudmestad, 1995;Zaldivar et al, 2001;Moreira et al, 2005;Okunowo et al, 2010), the series of macrocyclic trichothecenes such as epiroridin E, epi-isororidin E, roridin E, roridin H, trichoverrin A, trichoverrin B, verrucarin A and verrucarin J (Jarvis et al, 1985;Abbas et al, 2002). Wang et al (2007) confirmed that M. roridum produced mycotoxin in group trichothecenes namely Roridin and Isororidin.…”
Section: Discussionmentioning
confidence: 99%
“…In these fungal genera, several species of Myrothecium have been developed as a mycoherbicide for controlling the water hyacinth and others weeds such as M. roridum (Liyanage and Gunasekera, 1989), Myrothecium verrucaria (Hoagland et al, 2007;Okunowo et al, 2010). There are numerous enzymes that M. roridum can produce such as the cellulases enzyme, which hydrolyzes the β-1,4-D-glycosidic bonds within the cellulose molecules of the plant (Akiba et al, 1995;Baer and Gudmestad,1995;Zaldivar et al, 2001;Moreira et al, 2005;Okunowo et al, 2010). Mycotoxins are the series of macrocyclic trichothecenes such as epiroridin E, epiisororidin E, roridin E, roridin H, trichoverrin A, trichoverrin B, verrucarin A and verrucarin J (Jarvis et al, 1985;Abbas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%